Socialist mayors in the United States : governing in an era of municipal reform, 1900-1920 - Berman, David R. (Studies in government and public policy., 2022)
"The United States is known as a country that has been highly antagonistic to socialism of any form. Socialists have tended to be outsiders to the political system, mounting criticisms of the government without serving in elected office themselves. Despite this well-deserved reputation, there was a period of time in the United States in which Socialist politicians were prominent and active at the municipal level, holding office as government insiders. From around 1900 to 1920, Socialist mayors in over 200 small cities across the United States brought about meaningful improvements in the quality of life for people in their communities, playing an important role in the municipal reform movement that took place during this period. Despite the limitations of being associated with a minority party--particularly a party that divided into right and left wings over whether to pursue elected office in the United States--these mayors were largely successful in achieving innovative reforms and challenging the status quo. Socialist Mayors in the United States is the first comprehensive study of socialism nationwide during the Progressive Era"--